The Importance Of Equal Social Status In Choosing Spouse Reflected In William S. Maugham's Up At The Villa (1941): A Sociological Approach - Rohmah, Siti Nur; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
This study is about Equality of Social Status. The problem of this study is how importance of equal social status in choosing spouse is reflected in Up at the Villa novel. The object of this study is Up at the Villa novel by William Sommerset Maugham. It is analyzed by a sociological approach. This study belongs to qualitative research. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is the Up at the Villa novel and the secondary data is other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of this study shows the following conclusion. Based on analysis it is quite obvious that there is a close relation between this novel and the social reality in England in early middle twentieth century. William Sommerset Maugham wants to show social phenomena within society about equality of social status in terms of choosing spouse in England in early middle twentieth century through Up at the Villa